Developing and evaluating theory-based messages to promote foster care - Ferreira, S.; Graça, J.; Magalhães, E. (The Spanish Journal of Psychology, 2025)
Foster care is the preferred out-of-home placement for children at risk. However, the number of children in child protection systems exceeds the availability of foster families, highlighting the need for recruitment campaigns. Despite the growing development of such campaigns, their results have not been evaluated. This study aimed to design and experimentally evaluate messages to increase awareness, willingness, and intention to foster. Data were collected from 405 adults aged 25 years or older (Mage = 40.4, SD = 10.5, range 25–72; 67% women) in Portugal. The results revealed no differences in awareness, willingness, and intention between message conditions. However, the message that focused on dealing with and overcoming the anticipation of separation from the foster child elicited higher levels of transportation and perceived effectiveness compared to a baseline message. Additionally, transportation mediated the differences in perceived effectiveness, awareness, willingness, and intention between messages. These findings highlight the need for more research on narrative-based approaches to promote foster care.